2018
DOI: 10.1136/annrheumdis-2017-211631
|View full text |Cite
|
Sign up to set email alerts
|

A pivotal phase III, randomised, placebo-controlled study of belimumab in patients with systemic lupus erythematosus located in China, Japan and South Korea

Abstract: BackgroundIntravenous belimumab plus standard of care (SoC) is approved in the USA and Europe for treatment of active, autoantibody-positive systemic lupus erythematosus (SLE).MethodsThis phase III, multicentre, randomised, double-blind, placebo-controlled study (BEL113750; NCT01345253) was conducted in 49 centres across China, Japan and South Korea (May 2011–September 2015). Patients with SLE were randomised 2:1 to intravenous belimumab 10 mg/kg or placebo, plus SoC, every 4 weeks until Week 48. The primary e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
264
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 224 publications
(283 citation statements)
references
References 26 publications
19
264
0
Order By: Relevance
“…The subcutaneous belimumab study [9] had the same primary endpoint as the BLISS-studies and also succeeded in meeting it. Comparable with the ILLUMINATE-trials [5,6], there was a significantly higher proportion of SRI-5 to 8 responders 3 in the belimumab group. Time to the first severe flare as measured with the modified SLE flare index was also significantly greater in the belimumab group.…”
Section: Drugs That Are Already Approved For Sle Treatmentmentioning
confidence: 64%
See 2 more Smart Citations
“…The subcutaneous belimumab study [9] had the same primary endpoint as the BLISS-studies and also succeeded in meeting it. Comparable with the ILLUMINATE-trials [5,6], there was a significantly higher proportion of SRI-5 to 8 responders 3 in the belimumab group. Time to the first severe flare as measured with the modified SLE flare index was also significantly greater in the belimumab group.…”
Section: Drugs That Are Already Approved For Sle Treatmentmentioning
confidence: 64%
“…In this context, 19 articles were shortlisted from the illustrated research, 7 of those [5][6][7][8][9][10][11][12] were chosen for analysis. The drugs whose effects were analysed in this review are tabalumab (6,7), belimumab [7][8][9], atacicept [10] and epratuzumab [11].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The approval of belimumab for adults in Japan was based on the results of two pivotal phase 3 studies, including a study undertaken in Northeast Asia [6,8]. This phase 3, randomized, double-blind study (BEL113750; NCT01345253) was conducted in China, Japan, and South Korea to assess the efficacy and safety of belimumab 10 mg/kg IV every 4 weeks for 48 weeks, compared with placebo, both as add-on to standard of care in patients with SLE, 77% of whom were from China [8]. In this study, belimumab significantly reduced disease activity with a safety profile similar to that of placebo [8].…”
Section: Introductionmentioning
confidence: 99%
“…18 19 Significant benefits of RCI compared with placebo were observed in secondary analyses of total hybrid SLE Disease Activity Index (hSLEDAI), total British Isles Lupus Assessment Group-2004(BILAG-2004 and Cutaneous Lupus Erythematosus Disease Area and Severity Index (CLASI) scores at week 8; benefits were also significant in post hoc analyses of the SLE Responder Index-4 (SRI-4) at week 8. 18 The hSLEDAI is identical to the Safety of Estrogens in Lupus National Assessment-SLEDAI used in clinical trials for belimumab [19][20][21][22] but uses the proteinuria definition from the SLE Disease Activity Index-2000 (SLEDAI-2K). In a separate post hoc analysis of these pilot study data, treatment with RCI demonstrated sustained improvements in disease activity over the 52-week study period.…”
mentioning
confidence: 99%